Barriers to nurses providing psychosocial care in the Australian rural context. (4th December 2012) - Kenny, Amanda; Allenby, Ann
Abstract This study in Victoria, Australia examined issues that rural nurses face in the provision of psychosocial care. Researchers, across a diversity of fields, have argued that psychosocial care is inadequate. Current knowledge of psychosocial care in rural areas is limited, despite the centrality of nurses in the provision of this care. Using an interpretive descriptive design, four focus groups were conducted with 22 nurses from five rural hospitals. Thematic analysis resulted in the emergence of five organising themes that impact on the provision of psychosocial care: constructive relationships, professional isolation, multiskilling expectations, client interaction, and competing demands. The global theme, "Managing multiple roles, demands and relationships" reflected the notion that the provision of psychosocial care is impacted on by the multiple roles and tasks that rural nurses undertake and the impact of contextual and interpersonal relationships. Strategies are needed to support nurses in their role and while clinical supervision has been identified as potentially useful, attention must be given to strong leadership, the development of a positive culture, recognition of the centrality of client care, and evidence‐based education.